Sustaining social security - Martin Gonzalez-Eiras; Dirk Niepelt (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper analyzes the sustainability of intergenerational transfers in politico-economic equilibrium. Embedding electoral competition for the votes of old and young households in the standard Diamond (1965) OLG model, we find that intergenerational transfers naturally arise in a Markov perfect equilibrium, even in the absence of altruism, commitment, or trigger strategies. Not internalizing the negative effects of transfers for future generations, the political process partially resolves the distributive conflict between old and young voters by shifting some of the cost of social security to the unborn. As a consequence, transfers in politico-economic equilibrium are higher than what is socially optimal. Standard functional form assumptions yield closed-form solutions for the politico-economic equilibrium as well as the equilibrium supported by the Ramsey policy. The model predicts population ageing to lead to larger social security systems, but eventually lower benefits per retiree. Under realistic parameter values, it predicts a social-security tax rate close to the actual one, but higher than the Ramsey tax rate. Closed-form solutions for the case with endogenous labor supply, tax distortions, and multiple policy instruments prove the results to be robust.
Keywords: H55; E62; 330; social security; intergenerational transfers; probabilistic voting; Markov perfect equilibrium; saving; labor supply; Soziale Sicherung; Privater Transfer; Optimale Besteuerung; Sparen; Vollkommener Wettbewerb; Theorie